The divine campaigns : AD 1100-1200 - Time-Life Books (Amsterdam : Time-Life Books, 1989)
1. Civilization, Medieval--12th century.
Includes Index
Bibliography: p. 170-171.
Basic Ed. Students
Keywords: Twelfth century